The Children Left Behind: The Need for Public Policies to Meet the Needs of Children Orphaned by COVID-19 - Tendriana, Gine; Yuliani, Vani Pravita (KnE Social Sciences, 2022)
COVID-19 has had a huge impact on the social, cultural, economic, education, tourism, trade and other sectors in Indonesia. Of all of these, health and humanitarian issues are those most highlighted. This research involved a literature search of books, journal articles and manuscripts of government regulations. Discussing the death rate from COVID-19 is not only a question of how many people have lost their lives in Indonesia due to contracting the disease, but also of the conditions and survival of the families left behind, especially children who have lost their parents due to COVID-19. The psychological aspects of the families of COVID-19 victims have often been neglected. As yet, the Government still largely focuses on the sick or dead and has not paid much attention to the bereaved families, especially children, who are in dire need of assistance. In Indonesia, there are 11,045 children who have become orphans, fatherless, or motherless because their parents or caregivers died due to COVID-19.1 This raises concerns regarding how their clothing, food and shelter needs can be met, along with their needs related to the rights to education, physical and psychological health, and security and safety. Therefore, procedures, coordination, schemes for protecting children’s rights, and mitigation actions involving public policies must notice and meet the needs of children who have lost their parents due to the COVID-19 pandemic. Keywords: COVID-19, children, assistance, public policy